Pre-emptive methadone or tramadol analgesia for mastectomy and ovariohysterectomy in bitches - Uscategui, Ricardo A. R.; Tiosso, Caio; Moro, Juliana V.; Mostachio, Giuliano Q.; Padilha-Nakaghi, Luciana C.; Feliciano, Marcus A. R.; Vicente, Wilter R. R. (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: mastectomy and ovariohysterectomy (OVH) in bitches are critical surgeries and pain control can be challenging. Objective: to evaluate the efficacy of pre-emptive analgesia with methadone (MET) or tramadol (TRA) in postoperative pain intensity, cardiorespiratory effects, and anaesthetic/analgesic consumption in female dogs undergoing mastectomy and OVH. Methods: a prospective randomized blind clinical trial was used to evaluate 48 bitches of various breeds, aged 10 ± 3.7 years, weighing 16 ± 12 Kg, and with multiple mammary tumours. The animals were distributed in two groups: TRA group received 5 mg/Kg tramadol and MET group 0.5 mg/Kg methadone intramuscularly, 10 min prior to anaesthesia induction with propofol followed by maintenance with isoflurane. Heart (HR) and respiratory (RR) rates, mean arterial pressure (MAP), propofol induction dose (PID), oxyhemoglobin saturation (SpO2), end-tidal isoflurane concentration (EtISO), and carbon dioxide pressure (EtCO2) were measured during the intra-operative period. Post-operative pain was evaluated for 12 h and rated according to the Melbourne scale. Rescue analgesia (0.5 mg/Kg methadone, 2 mg/Kg lidocaine, or 0.01 mg/Kg/min ketamine IV) was given when necessary and post-operative analgesic consumption recorded. Statistical tests were used to compare treatments. Results: rescue analgesia requirements, pain score, PID and analgesic consumption were significantly lower (p<0.05) in MET group. The HR was higher in TRA group, while EtCO2 and MAP were higher in MET group (p<0.05). Conclusion: methadone was more effective than tramadol in pre-emptive analgesia but not completely adequate on controlling pain in bitches subjected to unilateral mastectomy and OVH. Methadone led to lower cardiovascular depression and lower propofol dose required for anesthesia induction. However, increased EtCO2 and special care with patient ventilation is advised.